The Worst, the Best, Ignoring All the Rest: The Rank Effect and Trading Behavior - Hartzmark, Samuel M. (Review of Financial Studies, 2015)
I document a new stylized fact about how investors trade assets: individuals are more likely to sell the extreme winning and extreme losing positions in their portfolio ("the rank effect"). This effect is not driven by firm-specific information, holding period or the level of returns itself, but is associated with the salience of extreme portfolio positions. The rank effect is exhibited by both retail traders and mutual fund managers. The effect indicates that trades in a given stock depend on how the stock compares to other positions in an investor's portfolio.